The Position of Customary Criminal Law in The Development of The Legal System in Indonesia Based on The Criminal Code Number 1 Of 2023 - Servasius Edwin Telaumbanua; Ismaidar Ismaidar; Suci Ramadani (Utan Kayu Publishing, 2025)
Customary Criminal Law (Hukum Pidana Adat) is an unwritten legal system that has long existed within indigenous communities and focuses on restoring social balance. Its existence has historically occupied a position of legal ambiguity, as it was not formally recognized in the old Penal Code (Wetboek van Strafrecht), which led to normative conflicts and legal uncertainty in practice. However, the enactment of Law Number 1 of 2023 concerning the Penal Code (KUHP) marks a significant milestone by recognizing the concept of living law (law that lives within society) as part of positive criminal law. This study aims to analyze the position and role of Customary Criminal Law following the implementation of the new Penal Code, focusing on two main aspects. First, it examines the position of Customary Criminal Law based on its norms and its implementation within the context of legal pluralism in Indonesia. Second, it explores the implications of the development of Customary Criminal Law within the national criminal law system, particularly in relation to the new Penal Code and the reforms of the Criminal Procedure Code (KUHAP). Using a normative juridical research method with legislative, conceptual, and case approaches, this study reviews various literature, court decisions, and dispute resolution practices in indigenous communities, including cases in Nias and Wamena. The results show that the recognition of living law in Articles 2 and 100 of Law Number 1 of 2023 provides formal legitimacy for Customary Criminal Law, transforming its status from mere social practice to a binding legal source.However, its implementation faces challenges, such as standardizing the process for proving the existence of customary law, ensuring the compatibility of customary sanctions with human rights principles, and harmonizing them with criminal procedural law. Therefore, clear technical regulations and synergy between law enforcement officials and customary institutions are required to establish an effective hybrid model, where restorative justice through customary law can be integrated with the state criminal justice system